1993
DOI: 10.1182/blood.v81.6.1457.1457
|View full text |Cite
|
Sign up to set email alerts
|

Granulocyte colony-stimulating factor induces hFc gamma RI (CD64 antigen)-positive neutrophils via an effect on myeloid precursor cells

Abstract: In this study we have examined hFc gamma RI expression during myelopoiesis. Normal bone marrow (BM) cells were found to express hFc gamma RI up to the metamyelocyte stage. A different Fc gamma RI expression pattern was observed in an in vitro model of myelopoiesis. Purified CD34-positive BM cells, cultured for 12 to 14 days with granulocyte colony-stimulating factor (G-CSF), differentiate into a population of mature granulocytic cells. In these cultures, in which hFc gamma RI was virtually absent on the initia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
22
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(25 citation statements)
references
References 41 publications
3
22
0
Order By: Relevance
“…Our data shows that FcRIII expression was reduced with all doses of rHuG-CSF by 96 h, for both FMLP and Staphylococcus epidermidis stimulated and unstimulated PMN, although these decreases were not statistically significant. This down-regulation of FcRIII expression in response to rHuG-CSF appeared to correlate with an increase in FcRI levels, which agrees with the observations of previous G-CSF studies with human PMN (Kerst et al, 1993b;Spiekermann et al, 1994). The exact mechanism and biological significance of this reduced surface expression of FcRIII is still unclear, although several theories exist.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Our data shows that FcRIII expression was reduced with all doses of rHuG-CSF by 96 h, for both FMLP and Staphylococcus epidermidis stimulated and unstimulated PMN, although these decreases were not statistically significant. This down-regulation of FcRIII expression in response to rHuG-CSF appeared to correlate with an increase in FcRI levels, which agrees with the observations of previous G-CSF studies with human PMN (Kerst et al, 1993b;Spiekermann et al, 1994). The exact mechanism and biological significance of this reduced surface expression of FcRIII is still unclear, although several theories exist.…”
Section: Discussionsupporting
confidence: 90%
“…The decrease in FcRIII expression seen in this study could have been due to rHuG-CSF induced proteolytic cleavage. Previous studies have, however, disputed this theory of shedding, the suggestion being that the reduction in FcRIII expression may be due to an increase in circulating immature PMN released from the bone marrow (Kerst et al, 1993b).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…FcRI/CD64 is a specific marker for granulo-monocytic progenitor cells (Olweus et al, 1995). Normal bone marrow cells express CD64 antigen up to the metamyelocyte stage of differentiation (Kerst et al, 1993). In the present study we found that the percentage of FcRI-positive neutrophils was increased in the H-MDS patients.…”
Section: Discussionsupporting
confidence: 61%
“…However, it is unlikely that this cytokine is responsible, since it also enhances FcRI expression by monocytes, which was not observed in these studies. Granulocytes from patients with myeloid leukaemia given granulocyte colony-stimulating factor (G-CSF) following bone marrow transplantation showed increased expression of FcRI, which the authors interpreted as due to immature granulocytes which were expressing the higher levels of FcRI [18]. Higher levels of G-CSF have been found in cord compared with adult serum [19].…”
Section: Expression Of Fcr By Granulocytesmentioning
confidence: 99%